Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T15:25:23+01:00
A)
4x-3=3x+5
4x-3x=5+3
x=8
b)
5x+2=7-3x
5x+3x=7-2
8x=5 /:8
x=5/8
c)
3(x-1)=0
3x-3=0
3x=3 /:3
x=1
d)
-6(x+1)=24
-6x-6=24
-6x=24+6
-6x=30 /:(-6)
x = -5
e)
-7(x-2)=3x-1
-7x+14=3x-1
-7x-3x=-1-14
-10x=-15 /:(-10)
x=15/10
x=1 5/10
x=1 1/2
f)
4(x-1)=6(1+x)
4x-4=6+6x
4x-6x=6+4
-2x=10 /:(-2)
x=-5
Pozdrawiam. ( :
1 5 1
2010-03-25T15:25:26+01:00
A)
4x-3 = 3x+5
4x-3x = 5+3
x = 8

b)
5x+2 = 7-3x
5x+3x = 7-2
8x = 5 |:8
x = 0,625

c)
3(x-1) = 0
3x-3 = 0
3x = 3 |:3
x = 1

d)
-6(x+1) = 24
-6x-6 = 24
-6x = 24+6
-6x = 30 |:(-6)
x = -5

e)
-7(x-2) = 3x-1
-7x+14 = 3x-1
-7x-3x = -1-14
-10x = -15 |:(-10)
x = 1,5

f)
4(x-1) = 6(1+x)
4x-4 = 6+6x
4x-6x = 6+4
-2x = 10 |:(-2)
x = -5
1 5 1
2010-03-25T15:28:32+01:00
4X-3=3X+5
2=x

5x+2=7-3x
2x=9 / : 2
x=4,5

3(x-1)=0
3x-3=0
3x=3/:3
x=1

-6(x+1)=24
-6x-6=24
-6x=18/:6
-x=3

e)-7(x-2)=3x-1
-7x+14=3x-1
-4x=13/:4
-x=3,25

4(x-1)=6(1+x)
4x-4=6+6x
-2x=-2 /:2
-x=1
1 3 1